Association of Esophageal Varices with Portal Vein Diameter More Than 13 mm in Chronic Liver Disease Patients - Muhammad, Ali; Khan, Andaleeb; Butt, Kamil Rehman; Khan, Jawad; Akbar, Fazal; Zubair, Usama Bin (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency and association of esophageal varices with diameter of portal vein more than 13 mm in patients of chronic liver disease (CLD). Study Design: Cross-sectional study. Place and Duration of Study: Department of Gastroenterology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Feb to Aug 2018. Methodology: The study included one hundred and sixty-one patients of chronic liver disease with portal vein diameter more than 13 mm. Patients with the history of variceal bleeding, prior variceal treatment and liver transplantation were excluded. A consultant radiologist performed the hepatobiliary ultrasound in all the patients to measure the portal vein diameter. The presence of esophageal varices was confirmed on upper GI endoscopy performed by the consultant gastroenterologist. Results: The mean age of the patients was 47.16 ± 9.36 years. Most of the patients included in our study 102 (63.35%) were between 46-65 years of age. Out of the 161 patients, 95 (59.01%) were males and 66 (40.99%) were females. Esophageal varices were found in 128 patients (79.50%) with chronic liver disease with portal vein diameter >13 mm. Age, gender, duration of illness and BMI had no relation with the presence of esophageal varices in our target population. Conclusion: Patients of CLD with portal diameter greater than 13 mm had more chance for the presence of esophageal varices in our study.